Le survivant sans le syndrome Schreber - Richard Figuier (Amnis)
Disaster is the theme of many studies, but what about survival and of the figure of the survivor? This issue is central in Mass and power, work in which Canetti questions the “bad” survival, responsible for the continuation of the logic of war. But is there any “good” survival? Coming back from the catastrophe is not enough to be an “authentic survivor”, according to Kafka’s expression. To achieve this, it is necessary to have exceeded, with PrimoLevi and Robert Antelme, the opposition of life as a continuous growth and of death as its horrible opposite, by the gift, in a shared poverty, of this found again life.